Penegakan Hukum terhadap Pelaku Tindak Pidana Pengoplos Tabung Gas LPG Bersubsidi - Ratna Sayyida; Suwari Akhmaddhian (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2022)
LPG is produced to meet the needs of domestic, industrial and transportation gas fuels. As time goes by, many LPG sales agents commit fraud in order to get double profits through games on the selling price of LPG and the volume of LPG gas, one of which happened in East Jakarta. This paper aims to find out how the Law Enforcement Against Perpetrators of Pengoplos Subsidized LPG Gas Cylinders in East Jakarta. The method used in this research is the normative juridical method using qualitative analysis with the data obtained in the form of secondary data obtained from the results of previous research, legislation and other legal sources. The results of this study are that the transfer and injection of 3 Kg LPG gas into 12 Kg LPG gas cylinders is a prohibited job because it does not comply with the specified standards, with threats as referred to in Article 62 paragraph 1 of Law Number 8 of 1999 Regarding Consumer Protection, the punishment is a maximum imprisonment of 5 (five) years or a maximum fine of Rp. 2,000,000,000.00 (two billion rupiah).